PERBANDINGAN PERMAINAN EDUKATIF DAN ANIMASI VIRTUAL TERHADAP HASIL BELAJAR MATEMATIKA DITINJAU DARI KEAKTIFAN SISWA - Eka Kurnia (LPPM Universitas Bina Bangsa, 2021)
This research aims to compare educational games and virtual animations to mathematics learning outcomes in terms of student activity. The research was conducted in the fourth grade of SDN Jatirangga I Bekasi. The sampling technique used cluster sampling technique. The method used is a quasi-experimental design method. Furthermore, the normality and homogeneity prerequisite tests were carried out to show the normal and homogeneous data groups. After that, hypothesis testing using two-way ANNAVA obtained interaction t count (I) = 4.03 at the significance level of 0.05 t table = 3.96 because tcount> ttable then Ho was rejected. Thus, it means is an interaction between learning media and student activity towards mathematics learning outcomes. Because there is an interaction, Tukey's further test is carried out which gets the first result, namely Qcount = 4.85 while at α 0.05 dbv1 = 4 and dbv2 = 20 indicates Q table = 3.96. because Qcount> Qtable then Ho is rejected, it can be concluded that there are differences in mathematics learning outcomes using educational games and virtual animation on the low category of student activity. The second Tukey test shows the results, namely Qcount = 0.84 and Qtable = 3.96. It is concluded that by 0.84 <3.96 or Qcount <Qtable then Ho is accepted, it can be concluded that there is no difference in learning outcomes of mathematics using educational games and virtual animation on high category student activity.